Pemahaman Sistem Akuntansi Pemerintah Untuk Meningkatkan Pertanggungjawaban Keuangan Instansi - Anggraini, Ratna; Hasanah, Nuramalia; Indriani, Susi; Arafat, M. Yasser; Nindito, Marsellisa (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2017)
The public demand for public transparency causes government accounting to be important. The greater the funds managed by the government the greater the demand for financial accountability as a form of financial transparency in government. The purpose of community service is firstly to understand the understanding of UNJ's financial department employees for the government accounting system, secondly to ensure the socialization of regulatory changes in the financial accountability of the institution is well understood by the finance staff, the third is to find solutions to the limited human resources that understand Accounting system of the financial section in the process of preparing financial statements.Participants attendes this training as many as 26 people, namely the representatives of the Central Finance Staff and Faculty of the State University of Jakarta, the results of the implementation of an understanding of the new government regulations on the preparation of financial statements and increasing the skills of participants in government financial accountability. Kewords: Government Accounting System, Institutional Accountability